Upaya Pemecahan Masalah Dalam Pembelajaran Matematika Untuk Meningkatkan Hasil Belajar Siswa MTsN 3 Kota Jambi - Cunus Sa'adah; Amir Mahmud (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
In this research, we are trying to find out whether problem solving is utilized in mathematics training to improve students' performance at MTsN 3 Jambi City Problem solving is done by focusing students' attention on a particular concern, encouraging them to analyze the problem, and getting them to learn about and discover solutions. Processing is the information means mixing mental processes and physical actions to arrive at a solution. the students' performance in mathematics proved' Significant correlation is shown by the findings of the seventh grade students" shows that 57.69% of the students scored below the Minimum Performance Criterion set, namely 76%." Students' ability to acquire different kinds of knowledge is deficient since the learning techniques utilized don't suit their learning needs. The state of students in this school when worksheet instruction is used without prior preparation is not only unacceptable, but unfair as well. Classroom analysis has been employed These studies were performed on MTsN 3 Jambi City College students During the period of April to June 2020, The experiment was carried out in two phases, phase I and phase II. This research concludes that problem-based learning solutions will benefit students' learning.